Can Nuclear Imaging of Activated Macrophages with Folic Acid-Based Radiotracers Serve as a Prognostic Means to Identify COVID-19 Patients at Risk? - Cristina Müller; Roger Schibli; Britta Maurer (MDPI AG, 2020)
Herein, we discuss the potential role of folic acid-based radiopharmaceuticals for macrophage imaging to support clinical decision-making in patients with COVID-19. Activated macrophages play an important role during coronavirus infections. Exuberant host responses, i.e., a cytokine storm with increase of macrophage-related cytokines, such as TNFα, IL-1β, and IL-6 can lead to life-threatening complications, such as acute respiratory distress syndrome (ARDS), which develops in approximately 20% of the patients. Diverse immune modulating therapies are currently being tested in clinical trials. In a preclinical proof-of-concept study in experimental interstitial lung disease, we showed the potential of 18F-AzaFol, an 18F-labeled folic acid-based radiotracer, as a specific novel imaging tool for the visualization and monitoring of macrophage-driven lung diseases. 18F-AzaFol binds to the folate receptor-beta (FRβ) that is expressed on activated macrophages involved in inflammatory conditions. In a recent multicenter cancer trial, 18F-AzaFol was successfully and safely applied (NCT03242993). It is supposed that the visualization of activated macrophage-related disease processes by folate radiotracer-based nuclear imaging can support clinical decision-making by identifying COVID-19 patients at risk of a severe disease progression with a potentially lethal outcome.